Peluang Dan Hambatan Pengadaan Program Kewirausahaan Di Jemaat Mandiri Protestan Nazareth Lonas - Sosinggih, Fredy; Mosooli, Ermin Alperiana; Labito, Alce Mariani (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2023)
The church's economic development should be a concern of the church. PJM-PB Congregation Mandiri Protestant Nazareth Lonas does not yet have an entrepreneurial program to increase the congregation's finances, impacting the church's independence. This study aims to determine the opportunities and obstacles to procuring an entrepreneurship program at the PJM-PB Congregational Mandiri Protestant Nazareth Lonas. This research was conducted in two stages; first, the qualitative method was used to obtain in-depth information. Second is the quantitative method as a supporting method with data collection techniques using questionnaires and structured interviews. In this study, researchers also used a comparative study to compare the opportunities and obstacles of church entrepreneurship with control variables, theology, entrepreneurial knowledge, human resources, natural resources, availability of capital, and availability of working capital. The study results show that the PJM-PB of the Nazareth Lonas Protestant Independent Congregation already has enough opportunities to hold a church entrepreneurship program. This can be seen from the variables of theology, entrepreneurial knowledge, and availability of human and natural resources. Barriers exist in the variables of business capital and infrastructure. However, these obstacles will likely be overcome with the availability of opportunity variables.